1990
DOI: 10.1002/j.1460-2075.1990.tb08240.x
|View full text |Cite
|
Sign up to set email alerts
|

Nucleosome assembly in vitro: separate histone transfer and synergistic interaction of native histone complexes purified from nuclei of Xenopus laevis oocytes.

Abstract: High speed supernatants of Xenopus laevis oocyte nuclei efficiently assemble DNA into nucleosomes in vitro under physiological salt conditions. The assembly activity cofractionates with two histone complexes composed of the acidic protein N1/N2 in complex with histones H3 and H4, and nucleoplasmin in complex with histones H2B and H2A. Both histone complexes have been purified and their nucleosome assembly activities have been analysed separately and in combination. While the histones from the N1/N2 complexes a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
68
0
3

Year Published

1992
1992
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 115 publications
(74 citation statements)
references
References 57 publications
3
68
0
3
Order By: Relevance
“…Demembranated Xenopus sperm were incubated in the extracts for 60 min, then isolated for examination of His-B4 binding to the linker DNA by both SDS͞PAGE of acid-extracted nucleosomal proteins and micrococcal nuclease digestion. PAGE analysis showed that, in extract either with or without His-xNAP-1, sperm chromatin proteins were exchanged with nucleosomal histones, including His-B4, with H2A replaced by H2AX (12), an H2A variant comigrating with H3 ( Fig. 2G; see also figure 2 in ref.…”
Section: Involvement Of Nap-1 In Nucleosome Assembly Of Sperm Chromatmentioning
confidence: 92%
See 2 more Smart Citations
“…Demembranated Xenopus sperm were incubated in the extracts for 60 min, then isolated for examination of His-B4 binding to the linker DNA by both SDS͞PAGE of acid-extracted nucleosomal proteins and micrococcal nuclease digestion. PAGE analysis showed that, in extract either with or without His-xNAP-1, sperm chromatin proteins were exchanged with nucleosomal histones, including His-B4, with H2A replaced by H2AX (12), an H2A variant comigrating with H3 ( Fig. 2G; see also figure 2 in ref.…”
Section: Involvement Of Nap-1 In Nucleosome Assembly Of Sperm Chromatmentioning
confidence: 92%
“…In Xenopus eggs, the core histones H2A-H2B and H3-H4 stored in the cytoplasm are associated with histone chaperones nucleoplasmin and N1͞N2, respectively (11,12). To investigate whether B4, the linker histone of Xenopus eggs (13)(14)(15), is found complexed to other proteins, egg extract was fractionated by gel filtration (Superose 12), and fractions were probed with Abs to B4.…”
Section: Incorporation Of Linker Histones Into Dinucleosomesmentioning
confidence: 99%
See 1 more Smart Citation
“…Our ability to do this is likely facilitated by the presence of ATP-independent nucleosome assembly factors in the egg extracts, which may greatly reduce barriers to assembly (and therefore to disassembly) of nucleosomes onto DNA. In Xenopus egg extracts, these factors are known: the protein nucleoplasmin is known to act primarily as a chaperone for histones H2A/B, proteins N1 and N2 are associated with H3/4 (Dilworth et al, 1987;Kleinschmidt et al, 1990;Laskey et al, 1993), whereas the protein NAP-1 is associated with the linker histone B4 the embryonic variant of H1 (Shintomi et al, 2005). Because they are ATP independent, these factors must mediate both assembly and disassembly processes: for example, yeast NAP-1 facilitates lateral "sliding" of nucleosomes along DNA through transient removal and replacement of H2A/B (Park et al, 2005), and it is known to play a role in formation of regularly spaced nucleosome arrays in more complex chromatin assembly reactions (Ito et al, 1996).…”
Section: Stall Force Of Assembly Reaction Indicates Nucleosome Assembmentioning
confidence: 99%
“…These extracts contain a mixture of enzymes competent to assemble not only nucleosomes but also active chromatin. Despite the high complexity of extract reactions, drugs and antibodies have been used to identify and study the contribution of specific proteins to chromatin structure and function (Dilworth et al, 1987;Kleinschmidt et al, 1990;Hirano and Mitchison, 1994;MacCallum et al, 2002;Maresca et al, 2005). Extracts diluted from 2.5-to 400-fold have been used to assemble chromatin onto single DNAs against low piconewton forces (Ladoux et al, 2000;Wagner et al, 2005).…”
Section: Introductionmentioning
confidence: 99%